Religious tourism as a factor of tourism development in Greece: A case study of the monastery of St. Nektarios on Aegina - Redžić, Dalibor (Hotel and Tourism Management, 2019)
The economic and political conditions prevailing both in Greece and around the world determine the overall development of all forms of tourism. The rapid development of specific forms of tourism, such as religious tourism, is gaining an increasing interest in the global tourism market. Religious tourism is one of the key factors for the development of the national economy, and it is also important because it represents the heritage for future generations of enormous cultural, ecological and social significance. Aegina island is characterized by rich natural and cultural resources that are recognizable for their authenticity and beauty, and as such are significant elements for the creation and development of specific forms of tourism. In a study of religious tourism in the St. Nektarios monastery on the island of Aegina, a study was conducted on the impact that religious tourism has on local development and the promotion of pilgrimage to the island of Aegina as a tourist destination of exceptional cultural and religious interest in the international tourist market. In addition, the paper emphasizes the importance of religious tourism as a specific form of tourism that contributes to the development of areas in which religious monuments are located.